Optimizing thermal properties and heat transfer in 3D biochar-embedded organic phase change materials for thermal energy storage - Yadav, Aman; Mahendran, Samykano; Pandey, A. K.; Kareri, Tareq; Kalidasan, B. (Elsevier, 2024)
Enhancing the thermal properties and light-absorbing capabilities of phase change materials (PCMs) through the utilization of environmentally friendly, economically viable biochar materials is pivotal for optimizing solar energy capture and utilization. Herewith, initially, a green, three-dimensional, eco-friendly carbon nano inclusion is synthesized from Prosopis juliflora through vacuum oven carbonization at 130 °C, followed by size reduction via ball milling, promising high-impact contributions. Subsequently, green-synthesized nano-inclusions are dispersed in PEG-1000, creating advanced nano-enhanced phase change materials with improved thermo-physical properties using a two-step ultrasonication technique for enhanced thermal conductivity. This innovative study comprehensively explores the morphological behaviour, chemical stability, optical absorptivity, thermal properties, and reliability of the PEG-PJ composite. Remarkably, present research revealed that the composite achieved its highest thermal conductivity, an impressive 0.49 W/m⋅K, at 0.7 wt% of 3-D (PJ) biochar. Notably, the melting temperatures of the PEG-PJ composites consistently ranged from 40.1 °C to 40.5 °C. At the same time, their latent heat capacities displayed a notable increase, ranging from 145 J/g to 152.7 J/g, marking a substantial enhancement of 3.968% and 1.758%, respectively. Furthermore, to confirm the reliability and consistency of experimental findings, 500 thermal cycles were performed. Additionally, a numerical analysis study is conducted by utilizing 2-D energy modelling software to simulate the heat transfer rate owing to the improved thermal conductivity of the developed PEG-PJ composite PCM compared to PEG-1000. In conclusion, developed composites optimize solar storage, improve building thermal control, and enhance industrial heat exchangers for sustainable innovation in energy.